On Skepticism in the Practice of the Profession of Auditor - Petraşcu Daniela; Cetină Ionel Marius (Studies in Business and Economics)
In recent years, professional skepticism is increasingly being studied as an important building block in internal auditing. As a consequence, auditing standards include limited references to the content of audit evidence that may also have some degree of professional skepticism (SAS 99 - Consideration of Fraud in a Financial Statement Audit, Auditing Standard No. 12 Identifying and Assessing Risks of Material Misstatement, AU 316.13: The importance of exercising professional skepticism). However, to date, the Institute of Internal Auditors (IIA) standards do not contain an explicit and detailed definition and do not involve a formal assessment of the professional skepticism of internal auditors. However, in the work carried out in public entities and firms in Romania, it can be observed that this aspect is particularly useful for auditing, and it is being given more and more attention. According to Mueller &Anderson (2002), the skeptical actions of auditors and their conduct are mainly due both to the challenges posed by the economic factor as a whole and to the very different situations encountered in each organization. Studies have also shown that high professional skepticism causes auditors to perform a greater amount of audit work, expand their information searches, assess a higher probability of fraud, and assign more weight to evidence of fraud.